MODEL PEMBELAJARAN STAD DALAM MENINGKATKAN PEMBELAJARAN IPAS KELAS IV DI SD NAMIRA PROBOLINGGO - Hanafi, Khofifah Dewi; Kasdriyanto, Didit Yulian; Qomariah, Ryzca Siti (Jurnal Pepadu, 2024)
This study examines the lack of collaboration and student participation in learning, as well as their reluctance to share ideas. A descriptive qualitative method was chosen, with data collected through observation, interviews, and documentation. This research aims to describe the application of the STAD Learning Model in the IPAS subject for fourth grade at SD Namira Kraksaan Probolinggo, focusing on the model's implementation, IPAS learning with the STAD model, and supporting and inhibiting factors. The findings indicate that the STAD Model is implemented through: material information, group formation, group and individual tests, evaluation, and reward provision. The results show that the STAD model has been used before the implementation of the Independent Curriculum. The main factors supporting and hindering are the teachers' understanding of the model, classroom management, infrastructure, student enthusiasm, and their understanding of STAD. The application of this model has increased cooperation, learning enthusiasm, and students' confidence in expressing opinions